Simulation Tools For Power Electronics Courses, Based In Java Technologies - Canesin, Carlos A.; Gonçalves, Flávio A. S.; Sampaio, Leonardo P. (Eletrônica de Potência, 2008)
This paper presents interactive power electronics educational tools. These interactive tools make use of the benefits of Java language to provide a dynamic and interactive approach in order to simulate steadystate idealized rectifiers (uncontrolled and controlled; single-phase and three-phase). Additionally, this paper discusses the development and the usage of the Java applet programs to assist the teaching of conventional power electronics rectifier circuits, and to serve as a first design tool for the basic laboratory experiments in the power electronics courses. Some results were confronted with a well-known simulator package in order to validate the developed interactive simulation applets.